PENINGKATAN KINERJA GURU MADRASAH MELALUI MODEL KEPEMIMPINAN BERBASIS ZURIAH (Studi Kasus pada Yayasan Miftahul Huda Jepara) - sukarman sukarman (Tarbawi : Jurnal Pendidikan Islam, 2016)
ABSTRACTThis study is aimed at determining the effectiveness of Zuriah-based leadership in improving teacher performance. This research is a case study on Islamic education foundation Miftahul Huda Jepara. This study uses Qualitative Descriptive approach to find how significant leaderhip model based on Zuriah is related to teacher performance. The method used is observation, interview and questionnaire. This study has showed that Zuriah-based leadership has a significant and effective influence on teacher performance. Keywords: teacher performance, Zuriah, leadership